2011
DOI: 10.1021/bi101642d
|View full text |Cite
|
Sign up to set email alerts
|

Methylthioinosine Phosphorylase fromPseudomonas aeruginosa. Structure and Annotation of a Novel Enzyme in Quorum Sensing

Abstract: The PA3004 gene of Pseudomonas aeruginosa PAO1 was originally annotated as a 5’-methylthioadenosine phosphorylase (MTAP). However, the PA3004 encoded protein uses 5’-methylthioinosine (MTI) as a preferred substrate and represents the only known example of a specific MTI phosphorylase (MTIP). MTIP does not utilize 5’-methylthioadenosine (MTA). Inosine is a weak substrate with a kcat/Km value 290-fold less than MTI and is the second best substrate identified. The crystal structure of P. aeruginosa MTIP (PaMTIP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 46 publications
(74 reference statements)
0
27
1
Order By: Relevance
“…Although MSMEG_0990 and Rv0535 have been annotated as probable MTAPs in M. smegmatis and M. tuberculosis, respectively, the current work describes the first characterization of a bacterial MTAP. Pseudomonas isolates were thought to possess MTAP (1); however, recent work in P. aeruginosa showed that the enzyme was actually a methylthioinosine phosphorylase instead of MTAP (15). Our preliminary characterization of M. smegmatis MTAP indicated that mycobacterial MTAP may be different from human MTAP.…”
Section: Discussionmentioning
confidence: 84%
“…Although MSMEG_0990 and Rv0535 have been annotated as probable MTAPs in M. smegmatis and M. tuberculosis, respectively, the current work describes the first characterization of a bacterial MTAP. Pseudomonas isolates were thought to possess MTAP (1); however, recent work in P. aeruginosa showed that the enzyme was actually a methylthioinosine phosphorylase instead of MTAP (15). Our preliminary characterization of M. smegmatis MTAP indicated that mycobacterial MTAP may be different from human MTAP.…”
Section: Discussionmentioning
confidence: 84%
“…specific for MTA (15) and not SAH or Ad, the middle branch (Fig. 2, middle bracket) contains the S. griseus SAHD which was found to be specific for SAH and not MTA or Ad (2).…”
Section: Resultsmentioning
confidence: 99%
“…The P. furiosus MTAP was found to catalyze the phosphorolysis of MTA and Ad, but it could also catalyze the phosphorolysis of inosine with a k cat /K m of 9.74 ϫ 10 3 M Ϫ1 s Ϫ1 (22). Recently, a 5=-methylthioinosine phosphorylase (MTIP) from Pseudomonas aeruginosa has been identified and characterized (15). Interestingly, MTIP was found to be competitively inhibited by 5=-methylthioadenosine, the annotated substrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Recently the activity of MTDIH against the newly described enzyme methylthioinosine phosphorylase (MTIP) has also been published and the potential of inhibitors of MTIP as antibiotics discussed. 23 …”
Section: Introductionmentioning
confidence: 99%